Horizontal Stacking of PAPhy_a Cisgenes in Barley Is a Potent Strategy for Increasing Mature Grain Phytase Activity - Holme, Inger Baeksted; Madsen, Claus Krogh; Wendt, Toni; Brinch-Pedersen, Henrik (Frontiers in Plant Science, 2020)
Mature grain phytase activity (MGPA) in the Triticea tribe cereals has evolved through gene duplications and neo-functionalization of the purple acid phosphatase phytase gene (PAPhy) in a common ancestor. Increased gene copy number of the PAPhy_a gene expressed during seed development has augmented the MGPA in cereals like rye and wheat. PAPhy_a phytase is highly stable and a potent enzyme in feed. However, barley only contains one HvPAPhy_a gene and the MGPA levels needs to be increased to substitute for the addition of microbial phytases to the feed. A substantial increase in MGPA for cisgenic barley was achieved with one extra homozygous HvPAPhy_a insert when the plants were grown in the greenhouse. In the current study, the stability of increased MGPA was confirmed in open field grown cisgenic barley. Furthermore, the gene dose response of phytase cisgenes from three different cisgenic barley plants were horizontially stacked. Cisgenic barley with 0, 1, 2, 3, 4 and 6 extra HvPAPhy_a inserts demonstrated a perfect positive linear correlation with the level of MGPA. The current study provides new insight into the potential of stacking of cisgenes in crops and suggests cisgene stacking as a versatile strategy for crop improvement.